Technology Content Analysis with Technometric Theory Approach to Improve Performance in Radiodiagnostic Installation - Bambang Guruh Irianto; Abdul Rahman; Herry Andayani (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Installation Radiodiagnostic RSU Haji Surabaya facilitated some medical equipment for disease examinations  and have three  technology criteria: Examination by high technology equipment   (single-slice CT Scan), examination by intermediate equipment (General x-ray ≤ 300 mA / 125 KV) and examination by simple equipment  (Portable Dental x-ray ≤ 8 mA / 70 KV). When viewed in terms of revenue contribution to the Hospital, Radiodiagnostic Installation revenue from 2008 to 2012 has decreased continuously.  The aim of research for  measuring the contribution of each component technology: Tehnoware, Humanware, Inforware, and Orgaware on radiodiagnostic installation with the basic technometric theory approach  using indicator TCC (Technology Contribution Coefficien). The final results showed that a gap is almost evenly from the three technology components Humanware = 0519, Inforware = 0.538, orgaware = 0.534, but the gap is greatest in technology components Technoware = (0387, 0258, 0168), meaning that the strategy development units Radiodiagnostic  Installation prioritized to increase in aspect Technoware (rejuvenation medical equipment). DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7676